Axillary lymph node involvement in primary invasive breast carcinoma in a center in Baghdad Province - Ruqayah Sameer Wais; Hussam Hasson Ali (Medical Journal of Babylon, 2021)
Introduction: Breast carcinoma is the most common malignancy in women and it has become a major health problem affecting women worldwide. In Iraq, breast carcinoma is still a major cause of health morbidity and mortality in women. Axillary lymph node metastasis is considered the most important factor affecting prognosis and management in patients with breast cancer. Objective: This study aimed to evaluate lymph node metastasis in cases of primary invasive breast carcinoma and to find if there was any association among lymph node involvement with type, grade, and tumor stage. Materials and Methods: This was cross-sectional study of 100 female patients with primary invasive breast carcinoma aged 25–88 years, which collected from the archive of the educational laboratory in Baghdad Medical City, Baghdad, Iraq from April 2018 to December 2020. Male patients were excluded from this study. Results: A total of 100 patients were included in this study; all were women with primary invasive breast cancer with different histopathological types (80% of cases were invasive ductal ca. NOS). The age range of the patients was between 25 and 88 years. A significant correlation was observed between lymph node stage and tumor pathological stage (tumor size). Conclusions: Most cases of primary invasive breast carcinoma had axillary lymph nodes metastasis, with a strong correlation between lymph node stage and tumor size. However, no association was found with tumor grade or tumor type that could be related to the small sample size of this study.